Impairment of Endothelium-Dependent Relaxation in Chronic Two-Kidney, One Clip Hypertensive Rats - Choi, Ki Chul (Korean J Intern Med, 1994)
OBJECTIVES: Hypertension is commonly associated with an endothelial dysfunction that may contribute to the rise in blood pressure. Little information has been available so far on the role of endothelium-derived nitric oxide(EDNO) in renin-dependent, 2-kidney, 1 clip(2KIC) hypertension. The present study was aimed to determine a role for EDNO in the development and maintenance of 2KIC hypertension. METHODS: The effects of blocking synthesis or supplementation with precursor of EDNO on the development of hypertension were determined in 2KIC rats. Vascular responses to acetyl-choline, nitroprusside, atrial natriuretic peptide and nifedipine were examined in 7-and 12-week hypertensive 2KIC rats. RESULTS: N(G)-nitro-L-arginine-methyl ester caused a sustained increase of blood pressure in normal rats, while it was only partially associated with a more pronounced increase of blood pressure in the developmental phase of hypertension in 2KIC rats. In 7-week and 12-week hypertensive rats, phenylephrine-induced contraction of the isolated thoracic aortic rings was more sensitive compared with control. Their acetylcholine-induced relaxation was attenuated while the responses to nitroprusside or atrial natriuretic peptide were unaltered. Although their blood pressure did not differ between 7-week and 12-week hypertensive groups, the attenuation in the acetylcholine-induced relaxation was more prominent in the latter with a longer duration of hypertension. Indomethacin did not affect the attenuated relaxation to acetylcholine. The relaxation response to nifedipine was more pronounced in 2KIC rats. CONCLUSION: These results indicate that EDNO has little influence of the 2KIC hypertension, at least during its developmental phase, which is associated with an activated renin-angiotensin system. The chronic stage of 2KIC hypertension, however, is associated with an endothelial dysfunction which may contribute to the enhanced vasoconstriction and sustained high blood pressure.